O populismo em David Landau - Tomazoni, Larissa Ribeiro (Cadernos Zygmunt Bauman, 2019)
RESENHA CRÍTICA DO ARTIGO: LANDAU, David. Populist Constitutions. University of Chicago Law Review, 2018, Forthcoming FSU College of Law, Public Law Research Paper No. 861